Exploring the Chemical Composition and Cytotoxic Effect of Hexane Extract of Aerial Portions of Iraqi Amaranthus viridis on A549 Cell-Line - Noor S Jaafar; Enas J. Kadhim (Iraqi Journal of Pharmaceutical Sciences, 2025)
Amaranthus viridis (green amaranth), is naturally grown in Iraq belongs to the Amaranthaceae family, and is considered pseudocereal. This herb displays various classes of secondary metabolites including polyphenols, and phytosterols, in addition to other types of terpenes and fatty derivatives. Anti-inflammatory, antioxidant, antidiabetic, cardioprotective, and hepatoprotective are among the evaluated and proven clinical activities. Recently herbal remedies have emerged as a noteworthy new therapeutic option for several cancers. The most common cause of cancer mortality in Iraq is lung cancer. Few previous studies stated the invitro anticancer effect of this herb on the MCF-7 breast cancer cell and against HepG2, B16F10 melanoma, and HT-29 cancer cells. In Iraq, there is no previous study regarding the phytochemistry and the cytotoxic effect of this herb despite its wide distribution. n.hexane extract of A. viridis whole aerial parts was prepared by maceration and Soxhlet extraction methods, and subjected to GC/MS and HPLC analysis to characterize and quantify its constituents mainly phytosterols.. In GC/MS, the total number of identified compounds was thirteen and seventeen, and the extraction yield was 0.66 %, and 1.017% for cold and hot hexane extract respectively. bis(2-ethylhexyl) phthalate was the major constituent in cold hexane extract. Omega-3 (9,12,15-Octadecatrienoic acid, (Z,Z,Z)-) was only detected in the cold extract. 2(4H)-Benzofuranone, 5,6,7,7a-tetrahydro-4,4,7a-trimethyl-, (R)- and squalene were identified in both extracts and at a higher proportion in hot extract. 9,12-Octadecadienoic acid (Z,Z), homosalate were only detected in hot hexane extract and for the first time in an Iraqi plant. HPLC analysis revealed the presence of campesterol, stigmasterol, spinasterol, and beta-sitosterol in greater amounts in the hot than cold extract. Campasterol is the least concentrated, while spinasterol is the most concentrated. Based on the result, hot hexane extract was evaluated for its invitro anticancer effect against the A549 cell line using MTT assay. Results from the MTT assay showed no cytotoxic effect for hot hexane extract and an IC50 value of 1393 μg/ml, which may be due to its antioxidant effect